Configuration Synthesis of Decoupled Parallel Mechanical Leg of Walking Machining Robot - Jiali Chen; Yong Xu; Wencai Liu (Jixie chuandong)
A kind of fully rotational decoupled and partly translational decoupled mechanical leg (PUPR-PUPR-PRPAS) is synthesized by combining the screw theory, the practical function of the robot and the motion transformation matrix of the mechanical leg. First, the DOF of mechanical leg is obtained by analyzed the practical function of walking machining robot. Then, the number of branches and the distribution of DOF on branches can be obtained according to DOF. Next, the actuation screw is used to obtain the driving screw with the aim of movement decoupling by analyzing the kinematics screw and constraint screw of the mechanical leg. The configuration synthesis of decoupled parallel mechanical leg is carried out with the practical function of the robots. The branches are selected out in those obtained configurations according to the norm of functions and coordination to constitute the primary configuration. Finally, the compound simplification is carried out among single-degree-of-freedom joint pairs of mechanical leg, and the simplified motion transformation matrix is analyzed. The third branch is further improved to determine the final configuration of the mechanical leg.